Cardiovascular function shows early impairment in asymptomatic adolescents diagnosed with type 1 diabetes mellitus: an ultrasound-derived myocardial work study - Ghirardo, Martina; Cattapan, Irene; Sabatino, Jolanda; Pozza, Alice; Fumanelli, Jennifer; Avesani, Martina; Gutierrez De Rubalcava Doblas, Joaquin; Moretti, Carlo; Castaldi, Biagio; Di Salvo, Giovanni (Frontiers in Cardiovascular Medicine, 2025)
Background: Cardiac dysfunction and endothelial damage are known complications of type 1 Diabetes Mellitus (T1D) that mainly affect adults. However, some studies showed that subclinical myocardial impairment is often present already during adolescence. Myocardial Work (MW) has emerged as an afterload independent tool allowing to early identify subclinical damages. The aim of our study was to provide a comprehensive non-invasive cardiovascular evaluation of T1D adolescent using both conventional and advanced echocardiography.Methods: We enrolled 31 T1D patients in between 13-19-year-old and in follow-up from at least 10 years at the Paediatric Diabetology Unit of our institution. For all patients we collected anthropometric data, lifestyle data, blood tests, parameters of glycaemic control and conventional and advanced echocardiographic measurements. MW parameters were then compared to data from 31 age and sexmatched healthy volunteers from our lab. Results: In our population parameters of glycaemic control showed suboptimal control. Diastolic parameters were in normal range for all the patients; however, E' velocities and left atrial diameter were significantly worse in patients with poorer glycaemic controls. Global longitudinal strain (GLS), Global Work Index (GWI) and Global Work Efficiency (GWE) were significantly lower in the T1D population compared to the healthy population (p value <0.001), whilst Global Wasted Work was significantly higher in the T1D population (p<0.001). Patients with stage 1 hypertension or prehypertensive state exhibited pathological Pulse Wave Velocities with values >8 m/s (>99 th percentile).Conclusions: To the best of the authors' knowledge, this was the first study to investigate MW in T1D adolescents. GLS and MW descriptive parameters showed subclinical cardiac damage already during this particular timeframe. Therefore, these tools should be integrated in the cardiovascular assessment of diabetic adolescents, while preventive strategies must be applied to maximize glycaemic and pressure control effectiveness.